Rancang Bangun Web Service Perpustakaan Universitas Sam Ratulangi - Bramwell A. Kasaedja; Rizal Sengkey; Oktavian A. Lantang (Universitas Sam Ratulangi, 2014)
Abstract - Library now has information that is stored in physical or digital form. Advances in technology are increasingly supporting the development of a modern library. UNSRAT have a Special Service Unit Library in each Faculty. With a lot of information that needs a library data management such as book catalog management, book-lending management and membership management, supported with interesting appearance and easy to understand. Thesis with the title